Lithium supplement agent and preparation method thereof, positive pole piece and battery
By covering the positive electrode lithium supplement with carbon materials and various metal elements, the problem of poor conductivity of existing lithium supplements is solved, and a higher specific capacity and better battery capacity retention rate is achieved.
Patent Information
- Application Number
- CN202411995679.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing positive electrode lithium supplement agent has poor conductivity, which affects the battery's capacity retention rate at a lower charging voltage.
A lithium supplement agent is used, which includes a lithium supplement agent body and a coating layer, which consists of a carbon material and at least two metal elements of Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg. The metal elements are dispersed in the carbon material and are prepared by solvothermal reaction and calcination carbonization.
The conductivity and surface stability of lithium supplement agents are improved, the deliquency potential is reduced, and the deliquency reaction kinetics are enhanced, thereby improving the specific capacity of lithium supplement agents and improving the capacity retention rate of the battery.
Smart Images

Figure CN119786612A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a lithium supplement and a preparation method thereof, a positive electrode sheet, and a battery. Background Art
[0002] When lithium-ion batteries are charged for the first time, it is inevitable that there will be processes such as the formation of SEI film (solid electrolyte interface phase), the shedding of negative electrode material particles, and the irreversible deposition of lithium metal, which consume active lithium ions from the positive electrode material, resulting in a reduction in the available energy of the battery. The irreversible capacity loss of the most widely used graphite negative electrode is greater than 6%, while for silicon-based and tin-based alloy negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 10% to 20% or more. Pre-lithiation technology includes negative electrode pre-lithiation and positive electrode lithium replenishment, that is, adding a lithium replenisher to the positive electrode and adding a lithium replenisher to the negative electrode. There are many types of positive electrode lithium replenishers, however, the existing positive electrode lithium replenishers generally have the problem of poor conductivity, which affects the specific capacity of the lithium replenisher at a lower charging voltage, and further affects the capacity retention rate of the battery containing it. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a lithium supplement and a preparation method thereof, a positive electrode sheet, and a battery. The lithium supplement provided by the present application has excellent specific capacity, thereby improving the capacity retention rate of the battery.
[0004] In a first aspect of the present invention, a lithium supplement is provided, comprising a lithium supplement body and a coating layer formed on at least a portion of the surface of the lithium supplement body, wherein the coating layer comprises a carbon material and at least two metal elements of Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg, and the metal elements are dispersed in the carbon material.
[0005] According to the lithium supplement agent of the above embodiment of the present invention, at least two metal elements and carbon materials in the coating layer can enhance the conductivity of the lithium supplement agent and the stability of the surface of the lithium supplement agent, reduce the delithiation potential of the lithium supplement agent, and effectively improve the delithiation reaction kinetics, thereby increasing the specific capacity of the lithium supplement agent, and further improving the capacity retention rate of the battery.
[0006] In addition, the lithium supplement according to the above embodiment of the present invention may also have the following additional technical features:
[0007] In some embodiments of the present invention, the coating layer includes the carbon material and two metal elements selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg. Thus, the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0008] In some embodiments of the present invention, the carbon material and two metal elements selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg are obtained by calcining and carbonizing a bimetallic organic framework compound. Thus, the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0009] In some embodiments of the present invention, the lithium supplement agent includes at least one of Li5FeO4, Li6CoO4, Li2NiO2, Li3N, Li2O, and LiF. Thus, the lithium supplement agent has excellent specific capacity and can improve the capacity retention rate of the battery.
[0010] In some embodiments of the present invention, the average thickness of the coating layer is 2nm-5nm. Thus, the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0011] In some embodiments of the present invention, based on the total mass of the lithium supplement, the mass of the coating layer accounts for 5%-20%. Thus, the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0012] In the second aspect of the present invention, the present invention proposes a method for preparing the above-mentioned lithium supplement. According to an embodiment of the present invention, the method comprises: dispersing soluble metal salts of at least two metals of Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg, and organic ligands in a solvent, mixing with the lithium supplement body, and solvent thermal reaction to obtain an intermediate; calcining and carbonizing the intermediate under a protective gas atmosphere to obtain the lithium supplement. As a result, the lithium supplement prepared by the embodiment of the present invention has excellent specific capacity and can improve the capacity retention rate of the battery.
[0013] In some embodiments of the present invention, the lithium supplement body includes Li5FeO4, and the preparation method of Li5FeO4 includes: mixing a lithium source and an iron source according to a molar ratio of lithium element to iron element of (5-7):1, ball milling, and sintering under a protective gas atmosphere to obtain Li5FeO4. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0014] In some embodiments of the present invention, the ball milling time is 5h-12h. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0015] In some embodiments of the present invention, the rotation speed of the ball mill is 450 rpm / min-550 rpm / min. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0016] In some embodiments of the present invention, the sintering includes: sintering at 400°C-550°C for 2h-8h, heating to 800°C-950°C and sintering for 2h-8h. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0017] In some embodiments of the present invention, the organic ligand includes at least one of dimethyl imidazole, 2-aminoterephthalic acid, terephthalic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, and imidazole. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0018] In some embodiments of the present invention, the solvent includes at least one of dimethylformamide, ethanol, methanol, and isopropanol. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0019] In some embodiments of the present invention, the mass ratio of the soluble metal salt to the lithium supplement body is (0.1-10): (20-65). Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0020] In some embodiments of the present invention, the temperature of the solvothermal reaction is 80° C.-200° C. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0021] In some embodiments of the present invention, the solvent thermal reaction time is 4h-24h. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0022] In some embodiments of the present invention, the temperature of the calcination and carbonization is 400° C.-900° C. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0023] In some embodiments of the present invention, the calcination and carbonization time is 3h-15h. Thus, the prepared lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0024] In the third aspect of the present invention, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the lithium supplement agent described in the first aspect of the present invention, or the lithium supplement agent prepared by the method described in the second aspect. Thus, a battery containing the positive electrode plate has excellent capacity.
[0025] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises the positive electrode sheet of the third aspect. The battery has excellent capacity.
[0026] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0028] Figure 1 The schematic diagram of the structure of the lithium supplement provided by the present invention is shown.
[0029] Figure 2 The scanning electron microscope image of the lithium supplement prepared in Example 1 of the present invention is shown.
[0030] Figure Number:
[0031] A lithium supplement 100 , a lithium supplement body 1 , and a coating layer 2 . DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0033] In a first aspect of the present invention, the present invention provides a lithium supplement 100, see Figure 1 The lithium supplement agent 100 includes a lithium supplement agent body 1 and a coating layer 2 formed on at least a portion of the surface of the lithium supplement agent body 1, wherein the coating layer 2 includes a carbon material and at least two metal elements of Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg, and the metal elements are dispersed in the carbon material.
[0034] According to the lithium supplement agent 100 of the above embodiment of the present invention, the at least two metal elements and the carbon material in the coating layer 2 can enhance the conductivity of the lithium supplement agent 100 and the stability of the surface of the lithium supplement agent 100. For the delithiation potential, the addition of the two metal elements changes the electronic structure of the lithium supplement agent body 1, and it will adjust the charge distribution of the atoms in the lithium supplement agent body 1, so that lithium ions are more easily released from the lithium supplement agent body 1. From an energy perspective, the addition of metal elements reduces the energy required for lithium ions to be released, thereby reducing the delithiation potential, reducing the delithiation potential of the lithium supplement agent 100, and effectively improving the delithiation reaction kinetics, thereby improving the specific capacity of the lithium supplement agent 100, and thus improving the capacity retention rate of the battery.
[0035] According to an embodiment of the present invention, the coating layer 2 includes a carbon material and two metal elements selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg. Thus, the two metal elements act synergistically, and in the bimetallic coating layer, the metal element acts as a catalyst, and the synergistic effect between the two metals can optimize the electronic structure of the catalytic active site, thereby improving the adsorption and desorption of the reaction intermediates, accelerating the reaction kinetics, and reducing the energy barrier. There is charge transfer between the metals in the bimetallic catalyst, which enhances the adsorption capacity of the reactants, reduces the reaction energy barrier, and can further improve the conductivity of the lithium supplement body 1, reduce the delithiation potential, and make the lithium supplement 100 have excellent specific capacity, which can improve the capacity retention rate of the battery.
[0036] According to an embodiment of the present invention, the carbon material and two metal elements among Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg are obtained by calcining and carbonizing a bimetallic organic framework compound. Therefore, the present application first coats the bimetallic organic framework compound (bimetallic MOFs) on the surface of the lithium supplement body 1, and then calcines and carbonizes it. The bimetallic doped carbon material generated in situ, the metal elements are dispersed in the carbon material, so that the obtained two metal elements and carbon material are more evenly distributed on the surface of the lithium supplement body 1, and the contact area with the lithium supplement body 1 is large, which can further improve the conductivity of the lithium supplement 100 and the stability of the surface of the lithium supplement 100, so that the lithium supplement 100 has a better specific capacity and can improve the capacity retention rate of the battery.
[0037] Taking Zn and Co as an example, doping two different metal elements into MOFs-derived porous NC catalysts can construct nitrogen-coordinated bimetallic active sites. This structure can not only increase the active sites, but also optimize the electronic structure of the catalytic material.
[0038] According to some embodiments of the present invention, the lithium supplement body 1 includes at least one of Li5FeO4, Li6CoO4, Li2NiO2, Li3N, Li2O, and LiF. By combining the lithium supplement body 1 with the carbon material coating layer 2 containing two metal elements, the conductivity of the lithium supplement body 1 can be further improved, and the delithiation potential can be reduced, so that the lithium supplement 100 has excellent specific capacity and can improve the capacity retention rate of the battery.
[0039] According to some embodiments of the present invention, the average thickness of the coating layer 2 is 2nm-5nm, for example, it can be 2nm, 3nm, 4nm, 5nm, etc. The average thickness of the coating layer 2 is controlled within the above range, which is sufficient to improve the overall conductivity of the lithium supplement 100 and reduce the delithiation potential, but the coating layer 2 is not too thick to affect the specific capacity of the lithium supplement 100, so that the lithium supplement 100 has excellent specific capacity and can improve the capacity retention rate of the battery.
[0040] According to some embodiments of the present invention, based on the total mass of the lithium supplement 100, the mass proportion of the coating layer 2 is 5%-20%. For example, it can be 5%, 10%, 15%, 20%, etc. The mass proportion of the coating layer 2 is controlled within the above range, which is sufficient to improve the overall conductivity of the lithium supplement 100 and reduce the lithium desorption potential, but does not affect the specific capacity of the lithium supplement 100 by making the coating layer 2 too much, so that the lithium supplement 100 has excellent specific capacity and can improve the capacity retention rate of the battery.
[0041] In the second aspect of the present invention, the present invention provides a method for preparing the lithium supplement agent described in the first aspect, comprising:
[0042] S1. Dispersing soluble metal salts of at least two metals among Zn, Co, Mo, Fe, Cu, Ni, Al and Mg and organic ligands in a solvent, mixing with the lithium supplement body, and subjecting to solvent thermal reaction to obtain an intermediate.
[0043] In this step, the lithium supplement body is added to the solution containing metal salt and organic ligand in advance, and a layer of bimetallic organic framework compound is formed on the surface of the lithium supplement body by solvent thermal reaction, so that the coating layer has better uniformity.
[0044] According to some embodiments of the present invention, the lithium supplement body includes Li5FeO4, and the preparation method of Li5FeO4 includes:
[0045] S10, mixing a lithium source and an iron source in a molar ratio of lithium to iron of (5-7):1, ball-milling, and sintering under a protective gas atmosphere to obtain Li5FeO4.
[0046] As an example, the molar ratio of lithium element to iron element may be 5:1, 6:1, 7:1, etc.
[0047] The Li5FeO4 prepared by the above method has a moderate ratio of lithium to iron, which can reduce the increase of side reactions caused by excessive lithium, resulting in incomplete reaction of lithium salt, and can also reduce the volatilization of lithium salt and lack of lithium salt during the reaction caused by too little lithium salt, which affects the final product performance, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0048] According to some embodiments of the present invention, the ball milling time is 5h-12h, for example, it can be 5h, 7h, 9h, 10h, 12h, etc. By controlling the ball milling time within the above range, the lithium element and the iron element can be evenly mixed, so as to obtain Li5FeO4 with excellent performance, reduce the delithiation potential, and make the lithium supplement have excellent specific capacity, which can improve the capacity retention rate of the battery.
[0049] According to some embodiments of the present invention, the rotation speed of the ball mill is 450rpm / min-550rpm / min, for example, it can be 450rpm / min, 500rpm / min, 550rpm / min, etc. By controlling the rotation speed of the ball mill within the above range, the lithium element and the iron element can be evenly mixed, so as to obtain Li5FeO4 with excellent performance, reduce the delithiation potential, make the lithium supplement have excellent specific capacity, and improve the capacity retention rate of the battery.
[0050] According to some embodiments of the present invention, the sintering includes: sintering at 400°C-550°C for 2h-8h, heating to 800°C-950°C for 2h-8h. For example, the sintering temperature at low temperature (400°C-550°C) is 400°C, 450°C, 500°C, 550°C, etc., the sintering time at low temperature is 2h, 4h, 5h, 7h, 8h, etc., the sintering temperature at high temperature (800°C-950°C) can be 800°C, 850°C, 900°C, 950°C, etc., the sintering time at high temperature can be 2h, 4h, 5h, 7h, 8h, etc., thus, low temperature sintering is first performed, and then high temperature sintering is performed. Low temperature sintering is conducive to Li5FeO4 nucleation, and high temperature sintering is conducive to growth, and finally Li5FeO4 with better morphology is obtained, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0051] According to some embodiments of the present invention, the organic ligand includes at least one of dimethyl imidazole, 2-aminoterephthalic acid, terephthalic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, and imidazole. The above organic ligand is easy to react with two soluble metal salts under solvent heating conditions to generate a bimetallic organic framework compound, which is coated on the surface of the lithium supplement body. After calcination and carbonization, a uniform coating layer containing bimetallic elements and carbon materials is formed on the surface of the lithium supplement body, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0052] According to some embodiments of the present invention, the solvent includes at least one of dimethylformamide, ethanol, methanol, and isopropanol. The above solvent is easy to dissolve soluble metal salts and is compatible with organic ligands, so as to generate a bimetallic organic framework compound, which is coated on the surface of the lithium supplement body. After calcination and carbonization, a uniform coating layer containing bimetallic elements and carbon materials is formed on the surface of the lithium supplement body, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0053] According to some embodiments of the present invention, the mass ratio of the soluble metal salt to the lithium supplement body is (0.1-10): (20-65), for example, it can be 0.1:20, 0.1:50, 0.1:65, 10:20, 10:40, 10:65, etc. The mass ratio of the soluble metal salt to the lithium supplement body is controlled within the above range, so as to obtain a lithium supplement with a reasonable ratio of the lithium supplement body and the coating layer, which is sufficient to improve the overall conductivity of the lithium supplement and reduce the delithiation potential, without causing too much coating layer to affect the specific capacity of the lithium supplement, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0054] According to some embodiments of the present invention, the temperature of the solvent thermal reaction is 80°C-200°C. For example, the temperature of the solvent thermal reactor can be 80°C, 100°C, 150°C, 200°C, etc. Controlling the temperature of the solvent thermal reaction within the above range is further conducive to the generation of a bimetallic organic framework compound, which is coated on the surface of the lithium supplement body. After calcination and carbonization, a uniform coating layer containing bimetallic elements and carbon materials is formed on the surface of the lithium supplement body, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0055] According to some embodiments of the present invention, the solvent thermal reaction time is 4h-24h, for example, it can be 4h, 5h, 10h, 20h, 24h, etc. Controlling the solvent thermal reaction time within the above range is further conducive to the generation of a bimetallic organic framework compound, which is coated on the surface of the lithium supplement body. After calcination and carbonization, a uniform coating layer containing bimetallic elements and carbon materials is formed on the surface of the lithium supplement body, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0056] According to some embodiments of the present invention, the calcination and carbonization temperature is 400°C-900°C. For example, the calcination temperature can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc. By controlling the calcination temperature within the above range, the bimetallic organic framework compound generated on the surface of the lithium supplement body can be fully carbonized to obtain uniformly distributed metal elements and carbon materials without destroying the structure of the lithium supplement, which can further reduce the delithiation potential, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0057] According to some embodiments of the present invention, the calcination and carbonization time is 3h-15h. For example, it can be 3h, 5h, 7h, 10h, 15h, etc. By controlling the calcination time within the above range, the bimetallic organic framework compound generated on the surface of the lithium supplement body can be fully carbonized to obtain uniformly distributed metal elements and carbon materials without destroying the structure of the lithium supplement, and the lithium desorption potential can be further reduced, so that the lithium supplement has excellent specific capacity and can improve the capacity retention rate of the battery.
[0058] In the third aspect of the present invention, the present invention provides a positive electrode plate, which includes the lithium supplement agent described in the first aspect of the present invention, or the lithium supplement agent prepared by the method described in the second aspect.
[0059] Therefore, the battery using the positive electrode sheet has excellent capacity.
[0060] Typically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0061] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0062] As an example, the positive electrode active material includes, but is not limited to, at least one of a metal oxide positive electrode active material, a polyanion positive electrode active material, a transition metal positive electrode active material, and an organic positive electrode active material.
[0063] As an example, the metal oxide positive electrode active material is not limited to lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium manganese-rich material, lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), ferroferric oxide (Fe3O4) and lithium vanadate.
[0064] As an example, the polyanion positive electrode active material includes but is not limited to at least one of lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium iron manganese phosphate, lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium phosphate (LiVOPO4), lithium cobalt phosphate (LiCoPO4), lithium nickel phosphate (LiNiPO4), lithium iron silicate (Li2FeSiO4), lithium ferrous fluorosulfate (LiFeSO4F), lithium iron borate (LiFeBO3) and lithium iron titanate (Li2FeTiO4).
[0065] As an example, the transition metal positive electrode active material includes but is not limited to at least one of iron trifluoride (FeF3), cobalt trifluoride (CoF3), nickel trifluoride (NiF3), titanium disulfide (TiS2), iron disulfide (FeS2), molybdenum disulfide (MoS2) and niobium triselenide (NbSe3).
[0066] As an example, the organic positive electrode active material includes but is not limited to at least one of a quinone molecular organic material and a nitrogen-containing organic material.
[0067] As an example, the quinone-based molecular organic material includes at least one of benzoquinone, anthraquinone, phenanthrenequinone, dithienobenzoquinone, dipyridobenzoquinone, difuranobenzoquinone, 2,6-dicarboxylic acid lithium anthraquinone, 2,7-dicarboxylic acid lithium phenanthrenequinone and 2,7-dicarboxylic acid lithium pyrene-4,5,9,10-tetraone.
[0068] As an example, the nitrogen-containing organic material includes, but is not limited to, at least one of pteridine, phenoloxazine, a pteridine derivative, and a phenoloxazine derivative.
[0069] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0070] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0071] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0072] In a fourth aspect of the present invention, the present invention provides a battery, including the battery of the third aspect of the present invention, whereby the battery provided by the present invention has excellent capacity.
[0073] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0074] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0075] According to some embodiments of the present invention, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0076] According to some embodiments of the present invention, the negative electrode active material includes but is not limited to at least one of graphite, graphene, soft carbon, hard carbon, elemental silicon, silicon-oxygen materials, silicon-carbon materials, silicon-nitrogen composite materials, silicon-based alloys, elemental tin, tin oxide compounds, tin-based alloys, lithium metal, lithium alloys, lithium titanium oxides, transition metal oxides and transition metal sulfides.
[0077] According to some embodiments of the present invention, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0078] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0079] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg sodium carboxymethyl cellulose (CMC-Na)).
[0080] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0081] The present invention has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0082] According to some embodiments of the present invention, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyolefin membrane, aromatic polyamide membrane, polytetrafluoroethylene membrane, and polyethersulfone membrane.
[0083] According to some embodiments of the present invention, the thickness of the isolation film may be 10 μm-12 μm, for example, 10 μm, 11 μm, 12 μm, etc.
[0084] According to some embodiments of the present invention, the electrolyte may be in liquid state or in solid state.
[0085] When the electrolyte is liquid, the electrolyte may include an organic solvent, a lithium salt, and optionally an additive.
[0086] According to some embodiments of the present invention, the organic solvent is selected from at least one of C3-C6 carbonate compounds, C3-C8 carboxylic acid ester compounds, sulfone compounds, and ether compounds. More preferably, the C3-C6 carbonate compounds are selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; the C3-C8 carboxylic acid ester compounds are selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, and propyl propionate; the sulfone compounds are selected from cyclopentane sulfone; and the ether compounds are selected from at least one of triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0087] According to some embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluorooxalatophosphate, and lithium bis(trifluoromethanesulfonyl)imide.
[0088] When the electrolyte is solid, the electrolyte includes a solid electrolyte and a lithium salt.
[0089] As an example, the solid electrolyte includes, but is not limited to, at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a boride solid electrolyte, and an ionic liquid.
[0090] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0091] Example 1
[0092] The first step: premix lithium hydroxide and ferric oxide materials in a ball mill according to a Li:Fe molar ratio of 5.5:1 for 5 hours, the ball mill speed is 450rpm / min, and then calcined at a first temperature of 500°C for 4 hours in a nitrogen atmosphere, and sintered at a second temperature of 900°C for 6 hours, with a heating rate of 2°C / min, and finally a lithium-rich lithium iron oxide material is prepared. The material is crushed and sieved to finally obtain a lithium-rich lithium iron oxide material with a particle size Dv50 of 10 microns.
[0093] Step 2: Dissolve 10 mmol of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 20 mmol of cobalt nitrate hexahydrate Co(NO3)2·6H2O in 80 ml of ethanol solution, the molar ratio of Zn(NO3)2·6H2O to Co(NO3)2·6H2O is 1:2, stir to dissolve, and then add 4 g of lithium-rich lithium ferrite material to obtain the first solution.
[0094] Step 3: Dissolve 4 g of dimethylimidazole in 40 ml of ethanol solution and stir to prepare a second solution. Add the first solution into the second solution and then add the mixture into a high-pressure reactor and react in an oven at 80° C. for 8 hours.
[0095] Step 4: Place the Zn / Co MOFs core-shell-coated lithium-rich lithium ferrite material prepared in the third step into a tubular furnace, and carbonize it at 800°C for 9 hours under a nitrogen atmosphere to finally prepare a lithium supplement coated with Zn / Co bimetallic and carbon materials.
[0096] Example 2
[0097] The first step: premix lithium hydroxide and ferric oxide materials in a ball mill according to a Li:Fe ratio of 6:1 for 6 hours at a ball mill speed of 500 rpm / min, then calcine at a first temperature of 500°C for 4 hours in a nitrogen atmosphere, and sinter at a second temperature of 900°C for 6 hours. The heating rate is 2°C / min to finally prepare a lithium-rich lithium iron oxide material. The material is crushed and sieved to finally obtain a lithium-rich lithium iron oxide material with a particle size Dv50 of 10 microns.
[0098] Step 2: Dissolve 1.08 g FeCl3·6H2O and 0.66 g H2BDC (phthalic acid) in 80 mL DMF and add 0.19 g Cu(NO3)2·3H2O, stir to dissolve, and then add 2 g lithium-rich lithium ferrite material.
[0099] Step 3: Transfer the solution from step 2 into a 100 mL polytetrafluoroethylene-lined autoclave and heat at 110 °C for 20 h.
[0100] Step 4: Place the Fe / Cu MOFs core-shell coated lithium-rich lithium ferrite material prepared in the third step into a tubular furnace, and carbonize it at 700°C for 10 hours under a nitrogen atmosphere to finally prepare a lithium supplement coated with Fe / Cu bimetallic and carbon materials.
[0101] The lithium supplements of Examples 3-7 and Comparative Examples 1-4 are the same as Example 1 except for different experimental parameters (see Table 1).
[0102] Among them, compared with Example 1, only 30 mmol of Zn(NO3)2·6H2O is used in Comparative Example 1, and Co(NO3)2·6H2O is not used. In Comparative Example 2, neither Zn(NO3)2·6H2O nor Co(NO3)2·6H2O is used. In Comparative Example 3, dimethylimidazole is not used. In Comparative Example 4, Li5FeO4 is directly used as a lithium supplement.
[0103] Some experimental parameters of the lithium supplements of Examples 1-7 and Comparative Examples 1-4 are shown in Table 1.
[0104] Table 1
[0105]
[0106]
[0107] “ / ” means none.
[0108] The lithium supplement prepared in Example 1 was subjected to a scanning electron microscope image to obtain Figure 2 It can be seen that the lithium supplement particles prepared in Example 1 are relatively regular and have a surface coating layer.
[0109] The lithium supplement agents of Examples 1-7 and Comparative Examples 1-4 were tested for specific capacity and prepared into batteries to determine the capacity retention rate of the batteries.
[0110] Preparation of positive electrode sheet: The above lithium supplement and lithium iron phosphate material are mixed at a ratio of 2:98 to obtain a positive electrode active material composite, which is mixed with conductive carbon and polyvinylidene fluoride binder at a ratio of 92:4:4, and an appropriate amount of NMP solvent is added dropwise. After grinding evenly, it is dispersed and coated on aluminum foil and vacuum dried at 110°C. After drying at room temperature, the aluminum foil is transferred to a blast oven at 120°C and dried for 12 hours, and then cold pressed and die-cut to form a positive electrode sheet.
[0111] Preparation of negative electrode sheet: Spherical hard carbon, binder PVDF, and conductive agent Super-P are mixed in a mass ratio of 97:2:1, dispersed in NMP organic solvent, and evenly coated on a copper foil with a thickness of 10μm. The aluminum foil is dried at 80℃ under vacuum conditions for 12h, and then cold pressed and die-cut to form a negative electrode sheet.
[0112] Electrolyte preparation: In a glove box filled with argon (water <10ppm, oxygen <1ppm), mix the solvent EC:EMC in a mass ratio of 1:1, quickly add fully dried LiPF6 to the mixed solution, mix thoroughly, and stir to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0113] Separator film: A 12 μm polyethylene film was used as the separator film.
[0114] Preparation of secondary batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrode sheets to isolate the positive and negative electrodes, wind them to obtain bare cells, weld the tabs, place the bare cells in an outer package, inject the above-prepared electrolyte into the dried cells, package, let stand, form, and shape them, and complete the preparation of secondary batteries.
[0115] Testing and analysis
[0116] Under the same conditions, the lithium supplement agents and batteries prepared in the above Examples 1-7 and Comparative Examples 1-4 were tested as follows, respectively. The specific testing methods are as follows:
[0117] Determination of specific capacity of lithium supplement agent: The lithium supplement agent: PVDF: conductive agent Super-P prepared above were mixed in a mass ratio of 6:2:2, and then dispersed into NMP solution, and then evenly ground and dispersed onto aluminum foil, and vacuum dried at 100°C. After drying at room temperature, the aluminum foil was transferred to a 120°C forced air oven and dried for 2 hours, and then cold pressed and die-cut to form a positive electrode sheet for button cell assembly, and a lithium sheet was used for the negative electrode sheet.
[0118] After the assembled button cell is left to stand for 12 hours, it is charged to 4.3V at a constant current and voltage of 0.05C, with a cut-off current of 0.02C, and then left to stand for 5 minutes. It is discharged to 2.5V at a constant current of 0.05C, and the released capacity is the specific capacity of the lithium supplement.
[0119] Battery capacity retention rate test after 100 cycles: 1C charge and discharge cycle test, voltage range is 2.75-3.65V, cycle 100 times, and measure the capacity retention rate.
[0120] The test results are shown in Table 2.
[0121] Table 2
[0122] Lithium supplement specific capacity (mAh / g) 100 cycles capacity retention rate Example 1 712 91.84% Example 2 710 91.97% Example 3 709 91.81% Example 4 701 90.89% Example 5 687 90.26% Example 6 690 90.49% Example 7 722 94.89% Comparative Example 1 688 88.15% Comparative Example 2 672 86.67% Comparative Example 3 645 82.38% Comparative Example 4 671 85.84%
[0123] Combining Table 1 and Table 2, it can be seen that the lithium supplement agent of Examples 1-7 of the present application has a high gram capacity of the lithium supplement agent, and the battery containing the lithium supplement agent has excellent cycle performance. Comparative Examples 1-4 do not use the lithium supplement agent of the present application, and the gram capacity of the lithium supplement agent and the cycle performance of the battery are significantly reduced. It can be seen that the lithium supplement agent provided by the present invention has an excellent specific capacity, and can improve the capacity retention rate of the battery.
[0124] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0125] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A lithium supplement, characterized in that: The lithium supplement agent includes a lithium supplement agent body and a coating layer formed on at least a portion of the surface of the lithium supplement agent body, wherein the coating layer includes a carbon material and at least two metal elements selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg; The metal element is dispersed in the carbon material.
2. The lithium supplement according to claim 1, characterized in that: The coating layer includes the carbon material and two metal elements selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg; Preferably, the carbon material and two metal elements selected from the group consisting of Zn, Co, Mo, Fe, Cu, Ni, Al and Mg are obtained by calcining and carbonizing a bimetallic organic framework compound.
3. The lithium supplement according to claim 1, characterized in that: The lithium supplement agent body includes at least one of Li5FeO4, Li6CoO4, Li2NiO2, Li3N, Li2O, and LiF.
4. The lithium supplement according to any one of claims 1 to 3, characterized in that: The average thickness of the coating layer is 2nm-5nm; Preferably, based on the total mass of the lithium supplement, the mass proportion of the coating layer is 5%-20%.
5. A method for preparing the lithium supplement according to any one of claims 1 to 4, characterized in that: The method comprises: Dispersing soluble metal salts of at least two metals selected from Zn, Co, Mo, Fe, Cu, Ni, Al, and Mg and organic ligands in a solvent, mixing with the lithium supplement body, and performing a solvent thermal reaction to obtain an intermediate; The intermediate is calcined and carbonized under a protective gas atmosphere to obtain the lithium supplement agent.
6. The method according to claim 5, characterized in that The lithium supplement agent body includes Li5FeO4, and the preparation method of Li5FeO4 includes: The lithium source and the iron source are mixed and ball-milled in a molar ratio of lithium element to iron element of (5-7):1, and sintered under a protective gas atmosphere to obtain Li5FeO4.
7. The method according to claim 6, characterized in that The ball milling time is 5h-12h; Preferably, the rotation speed of the ball mill is 450rpm / min-550rpm / min; Preferably, the sintering comprises: sintering at 400°C-550°C for 2h-8h, heating up to 800°C-950°C and sintering for 2h-8h.
8. The method according to any one of claims 5 to 7, characterized in that: The organic ligand includes at least one of dimethylimidazole, 2-aminoterephthalic acid, terephthalic acid, phthalic acid, terephthalic acid, isophthalic acid, isophthalic acid, and imidazole; Preferably, the solvent comprises at least one of dimethylformamide, ethanol, methanol and isopropanol; Preferably, the mass ratio of the soluble metal salt to the lithium supplement body is (0.1-10): (20-65); Preferably, the temperature of the solvent thermal reaction is 80°C-200°C; Preferably, the solvent thermal reaction time is 4h-24h.
9. The method according to any one of claims 5 to 7, characterized in that: The calcination and carbonization temperature is 400°C-900°C; Preferably, the calcination and carbonization time is 3h-15h.
10. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium supplement agent according to any one of claims 1 to 4, or a lithium supplement agent prepared by the method according to any one of claims 5 to 9.
11. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 10.
Citation Information
Patent Citations
Lithium-rich positive electrode material based on surface modification of MOFs and preparation method thereof
CN108336316A
Preparation method and application of lithium ion battery cathode lithium-supplement material Li5FeO4
CN109301242A
Method for in-situ construction of surface coating layer based on metal-organic framework material
CN112397690A
Negative electrode lithium supplementing component of lithium battery and preparation method of negative electrode lithium supplementing component
CN112952091A
Lithium supplement material precursor, lithium supplement material and preparation method and application of lithium supplement material
CN116730393A
Cited By
Positive current collector and preparation method thereof, positive plate, battery, battery pack and electric device
CN121394413A
Lithium-containing composite material and preparation method and application thereof
CN121662823A
A lithium-containing composite material, a preparation method and application thereof
CN121662823B